Optimal Location of Reclosers in the Primary Feeder "G" of the Cristianía Substation Belonging to Empresa Eléctrica Quito - Jiménez Jiménez, Diego Leonardo (2023)
Currently, the final consumer is more demanding with the quality of the electrical service, this implies that efficient equipment or elements that improve the electrical service must be used, protection and maneuver equipment must be introduced each time in the electrical networks to reduce the number of affected users. There are several alternatives to improve the continuity of electrical services, one of them is the so-called reconnection of electrical service, since it has been observed in several studies that 85% of the errors in the distribution networks are not permanent, after a time determining the error has been omitted, that is, the fault is cleared. With the objective of guaranteeing the continuity and reliability of the electrical energy supply to the users, in the present work the optimal location of recloser equipment in the electrical distribution system is analyzed.